The individual savings behaviour in Malaysian new villages - Tan, Alex Che Xin; Cheong, Wai Lorn; Chong, Chun Juen; Lee, Roger; Liou, Ye Hang (2019)
Malaysians are facing a low and stagnant income, which lead to a low rate of savings. The savings rate of household in rural area is usually lower than urban area. New village is one of the places in rural area which surrounded by Chinese communities. The objective of this study is to investigate the factors affecting the individual savings behaviour in Malaysian new villages. The independent variables include financial literacy, financial socialization agents and financial risk tolerance. In order to conduct informative research, questionnaire is constructed and distributed physically and electronically to 396 villagers in Johor new villages. The data are then gathered and rearranged in order to carry out extensive analysis on the pattern, causality, consistency and significance of the relationship between variables by using SPSS software. The results obtained from SPSS indicate that the financial literacy and financial socialization agents exhibit a significant relationship with savings behaviour. Nevertheless, financial risk tolerance shows a negative impact on savings behaviour. The results of this study are consistent with the expectation relationship.